Implementation of Digital Marketing for Household Businesses in the Context of Accelerating Economic Recovery During the Covid-19 Pandemic - Sakina Tantri; Etik Riyani; Ali Muktiyanto; Yeni Widiastuti; Agus Prasetyo (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to help small, household-based businesses accelerate their economic recovery. Household businesses in Ciledug District, Tangerang, Banten, are a potential sector that must be managed properly, especially in implementing marketing strategies using technology to survive and be sustainable. Therefore, it is important for the community service team to provide training regarding the implementation of digital marketing strategies for household businesses in an effort to accelerate economic recovery in Ciledug District, Tangerang, Banten, by maximizing the potential of household businesses in the region. This training was attended by 36 housewives who actively participated in running business and social activities. In this training, material is provided on marketing concepts and digital marketing practices for business products. The result of this community service is that the form of training in implementing digital marketing can be seen from two things, namely knowledge of marketing theory, and also skills in terms of implementing digital marketing.